Desenvolvimento industrial com participação estatal: experiências históricas e o caso do Brasil e da Coréia do Sul - Liesenberg, Luciano (2006)
This study aim to analyse the strategies of industrialization with state participation adopted in Brazil and South Korea, as well as evidencing that these strategies have also shown their relevance in developed countries. This theme was adopted to analise the effectiveness of state coordinated actions by promoting the industry despite of its interference on the mechanisms of market. The effectiveness of state interference is assumed to depend on the forms and the quality of the intervention. The first part of the study provides a historical interpretation of state coordenated development processes of industrialization in central economies. The conclusion is that this interference created competitive advantages to this economies, allowing the maintenance of dominant positions in the international trade. The second part ot the study focalize in a comparaty analise of the intervention in Brazil and South Korea. Whith this objective, specific policies were chosen to create a comparative basis: Politics of Financing, Credit and Subsidies; market protection policies, and Foreign Direct Investment incentives and tecnological absorption policies. The efectiveness of this policies was measured by the comparison of macroeconomic aggregates of the two contries. The results evidence that South Korea actieved long-run positive effects, wich provide to the country larger external projection and a more sustainable financial pattern of external indebtedness. External factors also demonstrate significant influence on the adoption and on the result of these politics. In Brazil, despite of the diversificated industrial structure created, the endogenous compound of grouth wasn´t created